2017
DOI: 10.1515/mmcks-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

A plea for quality in internship programmes – evidence from the business and administration students’ experience

Abstract: The career of business students is nowadays definitely influenced by their involvement in different internships and volunteering activities. The internship programmes help them understand the context of business organisations and decide what field of activity is most suitable for their professional life. However, sometimes internship programmes are not very well organised and influence in a negative manner students′ final perception of a certain domain. Our research identified and analysed the main factors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Internship can be considered as a path to smoothen out an entrant's process into the industry (Baltescu, 2016). Based on a study of a well-known Romanian business school, Goia et al (2017) have found that job arrangements, mentorship and employability benefits, learning content, academic supervision, bureaucracy and accessibility determine the quality of internship. Participation in shortterm internships, result in higher rates of job suitability, employability skills and professional expectations.…”
Section: Internship From the Perspective Of Mentorsmentioning
confidence: 99%
“…Internship can be considered as a path to smoothen out an entrant's process into the industry (Baltescu, 2016). Based on a study of a well-known Romanian business school, Goia et al (2017) have found that job arrangements, mentorship and employability benefits, learning content, academic supervision, bureaucracy and accessibility determine the quality of internship. Participation in shortterm internships, result in higher rates of job suitability, employability skills and professional expectations.…”
Section: Internship From the Perspective Of Mentorsmentioning
confidence: 99%
“…This was also highlighted by Heslin (2005), who studied the contextual and individual factors acting as antecedents of objective or subjective career success, proposing reference models, and discussing the perception of career success, based on referent choice (using social comparison theory), organizational interventions, and potential cultural differences. For students, the quality of internship programs (Goia, Marinas and Igret, 2017) and the international experience (Butum, 2017) play an important role in establishing career priorities. Bagdadli and Gianecchini (2019) have discussed three theoretical mechanisms (developmental, informational, and relational) when illustrating why and how organizational career management practices translate into career success.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Course context measures the elements of the course such as instruction (Abdulla, Mahmood, Fatah, 2019), quality of the course (Goia, Marinaș, and Igret, 2017), a form of review, class size, the language of the study (Joshi & Tyagi, 2019), teacher encouragement, rewards, and incentives (Abdulla, Mahmood, Fatah, 2019) that affected the motivation of the student in the knowledge. Diversity in team structure measuring team dimension and their role in knowledge transfer through a subordinate structure (Joshi & Tyagi, 2019), proper mentoring (Jaradat, 2017), mentoring among colleagues (Goia, Marinaș, and Igret, 2017), equal and balance the role of professionalism (Jaradat, 2017). The variable in diversity in team structure will encourage the management and coordinator to see how their student's ability to work in the team can lead to personal development.…”
Section: Environmental Factorsmentioning
confidence: 99%